Rapid muscle force capacity changes after soccer match play - Thorlund, J. B.; Aagaard, P.; Madsen, K. (International Journal of Sports Medicine, 2009)
The present study examined the fatigue development in muscle mechanical properties with emphasis on rapid force characteristics and neuromuscular activity in response to high level soccer match play. Young elite soccer players (n=9) were tested before (CON) and after (POST) a soccer match for maximal knee extensor and flexor isometric strength (MVC) and contractile rate of force development (RFD) with synchronous surface electromyography (EMG) recording. Furthermore, maximal vertical jump power and related parameters were assessed. Isometric knee extensor and flexor MVC decreased ~10% (p=0.01) along with a right-shift in the moment-time curve. RFD decreased ~9% (0-200 ms) for the knee flexors while there was a tendency towards reduced RFD during knee extension following soccer match play. Similar reductions were observed for some but not all selected EMG parameters during the MVC and RFD tests. Mechanical jump parameters generally remained unchanged post match play. This study is the first to examine the fatigue induced changes in rapid muscle force production (RFD) induced by soccer match play. The observed decrement in rapid muscle force capacity is likely to have negative impact on performance in explosive playing actions (i.e. accelerations, kicking, sprinting) that typically is involved in soccer match play.